THE FORMATION OF BUYING INTEREST IN WAKAME JAPANâS PRODUCT CITRA HAND AND BODY LOTION THAT IS AFFACTED BY THE ATTRACTION MESSAGE AND CELEBRITY ENDORSER (BASED ON SURVEY IN BOGOR) - Paojiah, Paojiah; Samsuri, Samsuri (JURNAL VISIONIDA, 2016)
PT. Unilever, Tbk with a product âCitraâ is a company that engaged in cosmetics. By using attraction message and celebrity endorser in selling their products, Citra has aims to increase the number of consumers buying interest. Survey research methods, forms of descriptive research and verification. There are 100 respondents as the object of the research. The secondary data obtains from the central statistical agency of Bogor and official website of Citra. The tests are conducted by validity, reliability, classic assumption, and likert scale for multiple linear regressions. The result shows that all indicators are valid and reliable, simultaniously attraction message (X1) and celebrity endorser (X2) affect on consumer buying interest of âCitra Wakame Japanâhandand body lotion (Y). Furthermore, based on partial variables show that attraction message (X1) was not affect consumer buying interest of hand and body lotion âCitra Wakame Japanâ (Y), while celebritry endorser (X2) has significant and positive impact on consumer buying interest on the âCitra Wakame Japanâ hand and body lotion (Y).Keyword: Attraction message, Celebrity Endorser, Buying Interest